Policy space conflicts in global trade politics - Xu, Qinyi; Guan, Chuanjing (Routledge, 2025)
Policy Space Conflicts in Global Trade Politics delves into the structure, driving forces and contemporary influencing factors of trade relations dynamics, providing insights into the present and future trajectories of the global trade order.The post-pandemic global governance challenges combined with the concurrent, if not concomitant, escalation of economic rivalries between great powers are catalysing a weakening of the liberal international order, undermining the very foundations upon which contemporary global production network is built. With the return of geopolitical tensions, the conflict over global governance versus state governance has again become the nexus where global trade politics are contested and negotiated. This book presents the Policy Space Conflict framework, an analytical framework that diverges from extant concepts of policy diffusion, power transition, socialisation and neo-liberal institutionalist models of analyses, and is instead advanced as a framework that renews the classic concept of 'policy space' - the space left for one to freely use preferred national policy instruments when integrated into the globalisation and institutionalisation process in the past decades. The tensions inherent in and arising from policy space can be captured in the term 'policy space conflict', illuminating the dynamic shifts regarding the convergence of rules under globalisation and de-convergence concerns of states. This book emphasises the underlying logic and motivating rationale that lie beneath the evolution of 'policy space conflict' by theoretically revisiting the concept, providing an overview of its forms in history since the Bretten Woods and transitions from market-oriented to strategy-based. This exploration is examined using case studies drawn from real-world trade politics, which encompasses discussions on the decline of multilateralism, the asymmetry in development between the Global South and Global North and China-US institutional contestation.This book will be of interest to scholars in the fields of international relations, law, political economy, political science, economics and international trade as well as a broad range of audiences who are concerned of global trade politics in times of global uncertainty.
Keywords: International trade -- Political aspects.; Geopolitics.; elektronické knihy; electronic books